2010
DOI: 10.1051/0004-6361/200913247
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing in H1413+117: disentangling line profile emission and absorption in a broad absorption line quasar

Abstract: On the basis of 16 years of spectroscopic observations of the four components of the gravitationally lensed broad absorption line (BAL) quasar H1413+117, covering the ultraviolet to visible rest-frame spectral range, we analyze the spectral differences observed in the P Cygni-type line profiles and have used the microlensing effect to derive new clues to the BAL profile formation. We first find that the absorption gradually decreases with time in all components and that this intrinsic variation is accompanied … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 67 publications
(104 reference statements)
1
48
0
Order By: Relevance
“…We emphasize as a caveat that MmD, at a given Doppler shift, cannot disentangle the case where a part of the line flux is magnified like the continuum while the other part is not microlensed at all, from the case where the line flux is microlensed but less magnified than the continuum, i.e., 1 < µ line < µ continuum (see Appendix A of Hutsemékers et al 2010). Nevertheless, when the line flux is entirely included in F Mµ (respectively in F M ) in some Doppler shift interval, it unambiguously indicates that this part of the line profile is magnified like the continuum (resp.…”
Section: Macro-micro Decomposition (Mmd)mentioning
confidence: 99%
“…We emphasize as a caveat that MmD, at a given Doppler shift, cannot disentangle the case where a part of the line flux is magnified like the continuum while the other part is not microlensed at all, from the case where the line flux is microlensed but less magnified than the continuum, i.e., 1 < µ line < µ continuum (see Appendix A of Hutsemékers et al 2010). Nevertheless, when the line flux is entirely included in F Mµ (respectively in F M ) in some Doppler shift interval, it unambiguously indicates that this part of the line profile is magnified like the continuum (resp.…”
Section: Macro-micro Decomposition (Mmd)mentioning
confidence: 99%
“…In order to provide a more global overview of the variety of signals which may be observed, we completed our main sample with five systems we studied elsewhere: SDSS J0924+0219 (Eigenbrod et al 2006a), H1413+117 (Hutsemékers et al 2010), J1131-1231 (Sluse et al 2007), HE 2149-2745 (Burud et al 2002), and Q2237+0305 (Eigenbrod et al 2008;Sluse et al 2011). This is not a complete list of known microlensed quasars (see e.g.…”
Section: The Extended Samplementioning
confidence: 99%
“…Following Sluse et al (2007) and Hutsemékers et al (2010), we assume that the spectrum of an observed lensed image F i is the superposition of 2 components, one component F M which is only macro-lensed and another one, F Mμ , both macro-and A62, page 6 of 28 Table 3. Physical quantities associated to the source quasar.…”
Section: Macro-micro Decomposition (Mmd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most micro-lensing activity is seen for the D component, which variability lasts for at least several years (Chartas et al 2004;Jovanović 2005). Moreover, the micro-lensing of the D component shows a chromatic dependence (Hutsemékers et al 2010). This result is directly consistent with the estimation of the duration of the micro-lensing events in H1413+117 by Witt, Mao & Schechter (1995).…”
Section: Introductionmentioning
confidence: 99%